Quantification of functional abilities in Rett syndrome: a comparison between stages III and IV - Monteiro, Carlos B. M.; Savelsbergh, Geert J. P.; Smorenburg, Ana R. P.; Graciani, Zodja; Torriani-Pasin, Camila; Abreu, Luiz Carlos de; Valenti, Vitor Engrácia [UNESP]; Kok, Fernando (Dove Medical Press Ltd, 2014)
We aimed to evaluate the functional abilities of persons with Rett syndrome (RTT) in stages III and IV. The group consisted of 60 females who had been diagnosed with RTT: 38 in stage III, mean age (years) of 9.14, with a standard deviation of 5.84 (minimum 2.2/maximum 26.4); and 22 in stage IV, mean age of 12.45, with a standard deviation of 6.17 (minimum 5.3/maximum 26.9). The evaluation was made using the Pediatric Evaluation of Disability Inventory, which has 197 items in the areas of self-care, mobility, and social function. The results showed that in the area of self-care, stage III and stage IV RTT persons had a level of 24.12 and 18.36 (P=0.002), respectively. In the area of mobility, stage III had 37.22 and stage IV had 14.64 (P<0.001), while in the area of social function, stage III had 17.72 and stage IV had 12.14 (P=0.016). In conclusion, although persons with stage III RTT have better functional abilities when compared with stage IV, the areas of mobility, self-care, and social function are quite affected, which shows a great functional dependency and need for help in basic activities of daily life.
Keywords: Rett syndrome; disability evaluation; self-care; mobility limitation